Olfactory and Gustatory Dysfunction as an Early Identifier of COVID‐19 in Adults and Children: An International Multicenter Study. (16th June 2020) - Qiu, Chenghao; Cui, Chong; Hautefort, Charlotte; Haehner, Antje; Zhao, Jun; Yao, Qi; Zeng, Hui; Nisenbaum, Eric J.; Liu, Li; Zhao, Yu; Zhang, Di; Levine, Corinna G.; et al.
Abstract : Objective: To evaluate the prevalence and characteristics of olfactory or gustatory dysfunction in coronavirus disease 2019 (COVID‐19) patients. Study Design: Multicenter case series. Setting: Five tertiary care hospitals (3 in China, 1 in France, 1 in Germany). Subjects and Methods: In total, 394 polymerase chain reaction (PCR)–confirmed COVID‐19‐positive patients were screened, and those with olfactory or gustatory dysfunction were included. Data including demographics, COVID‐19 severity, patient outcome, and the incidence and degree of olfactory and/or gustatory dysfunction were collected and analyzed. The Questionnaire of Olfactory Disorders (QOD) and visual analog scale (VAS) were used to quantify olfactory and gustatory dysfunction, respectively. All subjects at 1 hospital (Shanghai) without subjective olfactory complaints underwent objective testing. Results: Of 394 screened subjects, 161 (41%) reported olfactory and/or gustatory dysfunction and were included. Incidence of olfactory and/or gustatory disorders in Chinese (n = 239), German (n = 39), and French (n = 116) cohorts was 32%, 69%, and 49%, respectively. The median age of included subjects was 39 years, 92 of 161 (57%) were male, and 10 of 161 (6%) were children. Of included subjects, 10% had only olfactory or gustatory symptoms, and 19% had olfactory and/or gustatory complaints prior to any other COVID‐19 symptom. Of subjects with objective olfactory testing, 10 of 90 demonstrated abnormal chemosensory function despite reporting normal subjective olfaction. Forty‐three percent (44/102) of subjects with follow‐up showed symptomatic improvement in olfaction or gustation. Conclusions: Olfactory and/or gustatory disorders may represent early or isolated symptoms of severe acute respiratory syndrome coronavirus 2 infection. They may serve as a useful additional screening criterion, particularly for the identification of patients in the early stages of infection.